Respuestas
Respuesta dada por:
4
cotangente=
tangente=![\frac{sen \alpha }{cos \alpha } \frac{sen \alpha }{cos \alpha }](https://tex.z-dn.net/?f=+%5Cfrac%7Bsen+%5Calpha+%7D%7Bcos+%5Calpha+%7D+)
o tmb
tangente=![\frac{c.o}{c.a} \frac{c.o}{c.a}](https://tex.z-dn.net/?f=+%5Cfrac%7Bc.o%7D%7Bc.a%7D+)
cotangente=![\frac{c.a}{c.o} \frac{c.a}{c.o}](https://tex.z-dn.net/?f=+%5Cfrac%7Bc.a%7D%7Bc.o%7D+)
c.a(cateto adyacente)
c.o(cateto opuesto)
tangente=
o tmb
tangente=
cotangente=
c.a(cateto adyacente)
c.o(cateto opuesto)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años